2021
DOI: 10.1177/0957456521999874
|View full text |Cite
|
Sign up to set email alerts
|

Study on the collision dynamics of integral shroud blade for high-pressure turbine in different integral shroud clearance distance

Abstract: In steam turbine, turbine blades are prone to vibrate during operation, resulting in steam turbine accidents. The most common method for reducing the vibration of steam turbine blades is to design an integral shroud for blade which is termed as integral shroud blade. Most previous studies simplified straight integral blades into cantilever beam and used harmonic response analysis method to simulate the vibration response of blades. This method is suitable for simulating straight blade vibration under harmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Ren et al [ 3 ] investigated a coupled rotor-bearing system with touching and cracking faults to reveal its dynamic behavior. Zhang et al [ 4 ] studied the dynamic response of the turbine blades. Hong et al [ 5 ] studied the touch response of a single-disk rotor system under additional constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [ 3 ] investigated a coupled rotor-bearing system with touching and cracking faults to reveal its dynamic behavior. Zhang et al [ 4 ] studied the dynamic response of the turbine blades. Hong et al [ 5 ] studied the touch response of a single-disk rotor system under additional constraints.…”
Section: Introductionmentioning
confidence: 99%
“…For the study of shrouded blades with gaps, many scholars have established various models with shrouded blades to study the vibration characteristics of the system. [1][2][3][4][5][6][7] Szwedowicz et al 1 proposed a numerical calculation method for the forced vibration of a disk assembly considering the shroud friction effect. Numerical static analysis, free vibration analysis and forced vibration analysis were performed on the shrouded blade.…”
Section: Introductionmentioning
confidence: 99%
“…For the study of shroud gap, the mechanism of collision between twisted shrouded blades with asymmetric gap has been studied, 8 and the collision process of twisted shrouded blades with different gaps has been studied by using LS-DYNA software. 7 It is shown that the effects of the symmetric and asymmetric gap on blade vibration are different, and the motion between blades under asymmetric gap is more complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation